(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
Sustainable farming systems are being introduced to ensure optimum agricultural productivity despite climate change and environmental degradation. One such sustainable agricultural technology is conservation farming (CF). The uptake of this technology has remained low at about 5% years after its introduction. CF has five interrelated practices but for a variety of reasons, farmers are unable or unwilling to adopt all recommended practices. This study studied the agronomic effects of incomplete or partial conservation practice whereby not all the five practices are used, mimicking actual practices adopted by farmers. A split- plot design experiment involving partial or incomplete CF mainly use of basins, ripping were compared to conventional farming of normal ploughing (as main plots) and three crops - cowpea, millet and sorghum (split plot) was conducted. The objective was to determine the agronomic effects and efficacy of partial adoption of CF compared to conventional farming system. Data were collected on vegetative and reproductive parameters including, plant height, germination percentage, canopy density, number of leaves, number of branches/tillers/stems, SPAD (Soil Plant Analysis Development) readings a proxy for leaf chlorophyll content. Plants grown in basins had higher plant development (plant height, total biomass) and higher yields compared to those on conventional methods. This effect could be explained by better soil physical and chemical conditions in the basins as indicated by higher SPAD readings. Int. J. Agril. Res. Innov. Tech. 12(1): 115-119, June 2022